Biologic Therapy for Hidradenitis Suppurativa Plus Conglobate Acne Associated with SAPHO Syndrome: A Case Report - Kamilija Briede; Skaidra Valiukeviciene; Vesta Kucinskiene; Harald P.M. Gollnick (Medical Journals Sweden, 2020)
Abstract is missing (Short Communication)